2011
DOI: 10.1111/j.1600-9657.2011.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge level of primary school teachers regarding traumatic dental injuries and their emergency management before and after receiving an informative leaflet

Abstract: There is a clear need to inform teachers about traumatic dental injuries. The use of educational leaflets can be a successful and appropriate means of providing teachers with information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
94
3
32

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(143 citation statements)
references
References 23 publications
14
94
3
32
Order By: Relevance
“…Only 2.3% of Sudanese teacher chose milk as a proper storage medium, similar to results 4% obtained in Tanzania [13], 10% in Turkey [24], and 9% in Hong Kong [15].In contrast the current Table 6. Frequency of the teacher answers regarding the attitude evaluation with regard to dental trauma management.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Only 2.3% of Sudanese teacher chose milk as a proper storage medium, similar to results 4% obtained in Tanzania [13], 10% in Turkey [24], and 9% in Hong Kong [15].In contrast the current Table 6. Frequency of the teacher answers regarding the attitude evaluation with regard to dental trauma management.…”
Section: Discussioncontrasting
confidence: 47%
“…In table 4 answer about how would they clean the tooth after dental avulsion when it has fallen out, almost 24 In general when the teacher evaluated about the knowledge concerning traumatic dental injury it recorded that almost all of them (97%) had in adeque knowledge concerning tooth avulsion figure 5. Table 6 summarizes the responses to attitude questions.…”
Section: Knowledge Sectionmentioning
confidence: 99%
“…As (Table 3) shows, many of respondents (66.6%) said they would replant an avulsed tooth in the alveolar socket, which is not completely in line with previous studies [5][6][7]. Few teachers were able to determine the appropriate way for cleaning an avulsed tooth prior to replantation, that is in agreement with earlier studies [5][6][7]8]. In the present study, 33.3% of respondents stated that they would brush a dirty avulsed tooth before replanting it in its socket that is known to severely decrease the chance of achieving successful outcome.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies of outcomes of avulsed teeth have shown that the time elapsed between tooth avulsion and replantation, the higher the risk of replacement resorption and inflammatory root resorption [9]. Whereas proper replantation of an avulsed tooth within 30 min has been demonstrated to have a 90% chance of success [8], only a very low chance (5%) of longterm retention of an avulsed tooth exists if replantation occurs after 2 h [8]. It is discouraging to note that only 33.3% (n=9) of the teachers knew that professional help should be sought within 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Yaptığımız bu anket çalışmasında ebeveynlere yönelttiğimiz sorularla çocuklarında görülebilecek dental yaralanmalarla ilgili genel görüşlerini ve acil müdahale ile ilgili bilgi düzeylerini araştırmayı amaçladık. Elde edilen sonuçlar doğrultusunda yapılan pek çok çalışmada 8,[11][12][13][14] olduğu gibi bizim çalışmamızda da ebeveynlerin dental travma ve acil müdahale ile ilgili bilgi düzeylerinin yetersiz olduğu görülmektedir. Ebeveynler formal bilgiden ziyade kişisel görüşlerine göre tedavi hakkında fikir beyan etmişlerdir.…”
Section: Introductionunclassified